MASKNE - Prevalence and association of causative factors during Covid-19 pandemic at a tertiary care hospital of Karachi - Masood, Sadia; Unzela Ghulam; Zahra Rahmatullah; Shayana Rukhsar Hashmani (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the prevalence of mask acne in general population and healthcare workers, and the association of acne breakout due to mask-wearing with different factors. Method: The prospective, cross-sectional study was conducted from January to April 2022 at the Dermatology Department of Aga Khan University Hospital, Karachi, and comprised patients of both genders of all ages who received acne treatment during the period. Data was collected using a self-designed questionnaire having Cronbach’s alpha value 0.789 which was filled by the subjects. Data was analysed using SPSS 19. Result: Of the 200 subjects, 152(76%) were females and 48(24%) were males. The overall mean age was 25.50±8.49 years. There were 122(61%) non-healthcare workers and 76(38%) were healthcare workers. Acne was prevalent in 157(78.5%) participants, and, of them, 123(78.3) were females. Significant association of acne breakout due to mask-wearing was found with regular mask change habit (p<0.001) and past history of acne (p<0.01). Participants who wore mask continuously for 6 hours or more came up with more complaints of acne (p<0.05). Conclusion: Prolonged and continuous use of the same mask for 6 hours or more could lead to acne eruption. Key Words: Maskne, Healthcare worker, non-healthcare worker, HCW, non-HCW, Personal protective equipment, PPE.